Collaborative art, citizenship and childhoods: Cultural democracy and participatory design in the generation of common space - Ramírez Sanz, Angela; Vallejos Fabres, Cristóbal (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2026)
This article analyzes the work Espacio Público III, The Power of Representation by Ángela Ramírez Sanz, focusing on the interrelation between art, politics, and democracy. The project proposes the construction of new architectural spaces that emerge from a deliberative community and democratic process within rural environments, under a transdisciplinary approach that integrates these dimensions. Its innovative character is reflected in the participation of children and the co-construction of community spaces, highlighting the latter as a dynamic and transformative concept within contemporary political theory.The central hypothesis argues that Espacio Público III articulates an effective convergence between education, politics, and democracy, generating transformations in both the aesthetic and organizational spheres. This work not only redefines everyday experience through the creation of new spatialities, but also uses art as a key tool for the construction of social meanings, the strengthening of citizen participation, and the reconfiguration of community structures. Consequently, the analysis of this project reveals how artistic practices can play a fundamental role in shaping collective identities and building more inclusive and participatory societies.
Keywords: collaborative art; child participation; democracy; common space